Pencemaran Pb dan Cu pada Kerang Hijau di Pulau Pasaran, Lampung (Pollution of Pb and Cu in Green Mussel at Pasaran Island, Lampung) - Sagada Sangdiana Safitri (Program Studi Manajemen Sumber Daya Perairan, 2018)
The pollution of Pb and Cu has occurred in coastal areas of Bandar Lampung caused by metal manufacturing, shipyard, port activities, coal stockpiling and power plants. It was feared to cause accumulation of Pb and Cu in green mussels cultivated around Pasaran Island. This study aimed to analyze metals of Pb and Cu in body water of Pasaran Island and shellfish using the MP-AES method. The results showed that the highest concentrations of Pb and Cu in body water were 0.63 mg / l and 0.14 mg / l respectively. The highest concentrations of Pb and Cu in green mussels tissues were 8.45 mg / kg and 14.32 mg / kg. This condition showed that the Pb concentration has exceeded the allowed thresold so it was feared impact to health problems for the community. Keywords: Metals, concentration, Pasaran Island, green mussel